Analisis Kepuasan Petani Terhadap Program Makmur Pt Pupuk Kujang Di Kecamatan Pedes Dan Kecamatan Tempuran Kabupaten Karawang - Fawwaz, Andhika Nadhif; Sulandjari, Kuswarini; Wijaya, I Putu Eka (Jurnal Ilmiah Wahana Pendidikan, 2024)
PT Pupuk Kujang Cikampek created the Makmur Program as a solution for farmers by providing capital assistance, provision of means and supplies, as well as intensive support and involving an integrated supply chain, the success of an agricultural program depends not only on the proper implementation and allocation of resources, but also on the level of farmers satisfaction with the program. The research is aimed at analyzing the level of interest of farmers, level of performance of the Prosperity Program in Pedes district and Karawang district combat. The researchers identified 30 people as respondents using a saturated sampling method, a measurement scale using a likert scale. Data analysis in this study using Importance Perfomance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the research were: 1) The highest value of interest scores were found on the reliability variable of the attribute B10 and assurance variable 16. 2) The score with the highest overall performance value was on the agronomics' ease of contact responsiveness variable C11 with a total score of 145 and an average score of 4.83. 3) The Wealth Program has a satisfaction index of 70.94% and falls within the satisfaction category. 4) The primary priority level of the wealth Program is on the Attribute D18 (Wealth Program Partner Sale Price Assurance) with the average interest score obtained in this attribute of 144 and the average performance value of 67.